Rain, Snow, and Ice - Chappell, Rachel; Nang Chan Yeema (Bethany, MO USA Fitzgerald Books, 2007)
Illustrations and text introduce the weather and focus on rain, snow, and ice, from what they are, to why they form.
Keywords: Juvenile Nonfiction